La incomodidad de ser maestro en Colombia (2015)
This article is a reflection that arises from everyday school activities. It aims to identify some discomforts experienced in school and in society that affect the daily work of teachers, inside and outside the education center, documented through literary, educational, and film texts. It also aims to describe the vicissitudinous relationship of teachers with public and private entities, for instance, in health service. It seeks to expose anxieties and the complexity of tasks that are assigned to teachers and schools today, distanced from contemporary pedagogical sense. It is an approach to the once-used similes of lamented emergencies and forced silences, affirmed in the 21st century. The article examines the metaphor of the dragon hunter, the Sunday afternoon syndrome, and Hadrian’s syndrome with respect to the tense relations with family, colleagues, students, society, the State, and with learning environments. The content of the paper is not idealized; it could seem very pessimistic, but, paraphrasing the Spanish writer Antonio Gala, the article could say: “I am not pessimistic. I am a well-informed optimist.”